UML 2 certification guide fundamental and intermediate exams - Weilkiens, Tim.; Oestereich, Bernd (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2007)
The popular Unified Modeling Language (UML) is both a language and notation developed by the Object Management Group (OMG) used to design and create specifications for software systems. With the recent release of version 2.0 UML, the OMG has started the OMG-Certified UML Professional Program to provide an objective measure of UML knowledge. As a certified UML professional a developer has an important credential to present to employers and clients. Certification also benefits companies looking for skilled UML practitioners by giving them a basis for making hiring and promotion decisions. UML 2 Certification Guide is the only official study guide to passing the new UML exams. This book systematically covers all of the topics covered in the exams, and has been carefully reviewed by the OMG. The book begins by assuming only a basic knowledge of UML and then progresses far enough to allow a reader to pass both the fundamental and the intermediate level exams. Along the way the book also covers topics that are not in introductory books on UML but that are necessary to pass the exams. Tim Weilkiens is considered one of the top ten experts on UML, and both authors have extensive experience training developers to successfully take the exams. * The official certification resource * Assumes a basic knowledge of UML so that you can focus immediately on the exams * Written by two authors known for their skill as trainers, consultants, and developers * Developed systematically to enable you to master all exam topicswithout exception * Covers the use of UML for applications, as required by the exams, both inside and outside of the realm of software development * Includes a practice exam, glossary, list of books, and website information.
Foreword by Richard Soley; Foreword by Ivar Jacobson; 1 Introduction; 2 Fundamental; 3 Intermediate; Glossary; Sample Exams; Answers; Index.
Includes bibliographical references (p. 283) and index.
Keywords: Electronic data processing personnel -- Certification; Computer software -- Development -- Examinations -- Study guides; UML (Computer science) -- Examinations -- Study guides; Electronic books